Chopin [soundrecording]. - Chopin, Frederic (South San Francisco, CA : Selectmedia Entertainment, 2005)
Ever wonder who composed that tune you've heard before? Even if we were not aware of it, all of us grew up listening to classical music in cartoons, movies, and other settings. With our new series, Heard Before Classical Hits, you'll be sure to recognize the relaxing, uplifting, and beautiful classical music we're all familiar with. Enjoy!
Content: Ballade No. 1 -- Fantasia Impromptu, Op. 66 -- Grand Valse, Op. 42 -- Grand Valse Brilliante, Op. 18 -- Mazurka, Op. 63, No. 3 -- Nocturnes -- Preludes, Op. 28